Individual Aspects in the Process of Folklorization of Minor Verbal Forms (Based on the analysis of Sirian dialect Arabic proverbs with Georgian Parallels) - Tumanishvili, Khatuna ("Intercultural Dialogues" Transactions, 2023)
The Article presents considerations on the problem of individual role in minor forms of folklore, specifically in the genre of proverb. The fact that verbal folklore, unlike written, is in permanent colloquial circulation, is a major determinant for its dynamic development and frequent transformation. Proverbs, compared to other verbal folklore genres, are more stable and durable due to their stylistically concise and concentrated forms. However, the mentioned process of varying forms, deriving from their topical basis also occurs in the genre of proverbs. Analysis of the illustrative material utilized in this article, identified possible determinants for proverbs’ transformations (modifications, individual interpretations etc.). It has also been found that concrete folklore samples are changeable, which proves that each folklore piece has more than one author. Authors of the original ideas, known or anonymous, can be individuals, who lose their authorship with time. If ideas are valuable, communities identify, accept (unacceptable ones are rejected) and repeat them (sometimes with variations on the given theme). This is a process of individual cognition, collective recurrence of observations; retention, or rather `conservation” of the functionally essential ideas within the pool of most important national values, pertaining to the given ethnicity; the ideas, which are then passed from generation to generation through folklore. these ideas are then respectively identified as ideas contaning popular or national values. this article compares illustrative samples of Syrian-Arabic dialectal proverbs with their Georgian equivalents _ parallels that are at times complete or dynamic. Non-Arabic materials are obtained from sources in Syria, whereas no other foreign sources have been used.